Arthropod communities of rice agroecosystems can be shaped both by local agricultural practices and the surrounding landscape - Chen, Jia-Hsuan; Liao, Yi-Chang; Chiu, Ming-Chi; Yang, Man-Miao (Frontiers in Environmental Science, 2023)
Both intensive farming of paddy field crops and conventional farm management techniques have been a major cause of environmental issues in recent years. A more ecosystem-based, sustainable agricultural methodology should be utilized to help solve this dilemma. However, the joint effects of landscape and farming on arthropod communities in paddy fields are unexplored. In eco-friendly paddy fields, we postulate the arthropod diversity to be higher in fields that use ecosystem-based methods. In this study, we collected arthropods monthly using a blower-vac during the first rice crop of 2019 in Taiwan. A total of 53,522 individuals of 14 orders, 96 families, and 445 morphospecies were collected. All arthropods were identified into four functional groups. The result showed that insect communities are different between sustainable and conventional fields. Results showed that sustainable fields had a higher abundance of arthropod fauna than conventional fields. It was also apparent that the arthropod community changed along with the developmental growth of rice and in different areas. Three functional groups, viz., herbivores, parasitoids, and detritivores, present the best model when the farming type was assigned as the fixed effect, while the predator reveal the best model when the farming type, landscape, and their interaction were assigned as the fixed effects. The arthropod communities have also been affected by the surrounding landscape. This study reveals that both agricultural management and landscape can have a joint effect on arthropod communities in paddy fields.